2018
DOI: 10.2214/ajr.18.19599
|View full text |Cite
|
Sign up to set email alerts
|

Transjejunostomy Stent Placement in Patients With Malignant Small-Bowel Obstructions

Abstract: Transjejunostomy stent placement is an effective treatment in patients with malignant SBOs. It is technically feasible in most patients (95.7%) and provides substantial symptomatic improvement. Procedure-related complications are not rare but can be managed conservatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The 57 observational studies 45 101 reported on the treatment of 12,587 patients, 92% of which were patients with malignant bowel obstruction. Of these palliative patients, 27% underwent surgery for their obstruction (initially or after temporary stenting) and 73% were inoperable.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 57 observational studies 45 101 reported on the treatment of 12,587 patients, 92% of which were patients with malignant bowel obstruction. Of these palliative patients, 27% underwent surgery for their obstruction (initially or after temporary stenting) and 73% were inoperable.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment-related preferences or goals of care expressed by study participants rather than clinicians were referred to in the descriptive text of 15% of studies. 34 , 48 , 50 52 , 59 , 66 , 68 , 69 , 72 , 85 , 86 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stenting in jejuno-ileal obstructions is less common but has shown feasibility in limited series via percutaneous jejunostomy under IR guidance. 74 Although not mentioned explicitly in the pathway, experts in the consensus suggested the consideration for endoscopic lumen apposing metallic stent (LAMS)assisted gastro-jejunal or entero-enteric bypass for gastric outlet or more distal obstructions, respectively, as an alternative option for palliation. [75][76][77] The block version in round I lacked clarity regarding the selection of definitive surgical interventions and SEMS and yielded low consensus initially.…”
Section: Stentingmentioning
confidence: 99%